PENGARUH MODEL STEM TERHADAP HASIL BELAJAR SISWA TEMA 6 SUBTEMA 1 MATERI SUHU DAN KALOR KELAS V SD NEGERI 1 BATURSARI - Afif Asyarofi; Fine Reffiane; Moh. Aniq Khairul Basyar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that drives this research is the low learning outcomes of class V students. This is because teachers have not used STEM learning models which can improve learning outcomes. The problem in this research is whether the STEM model has an effect on student learning outcomes in Theme 6 subtheme 1 temperature and heat material for class V SD Negeri 1 Batursari? The aim achieved in this research is to determine the influence of the STEM model to improve student learning outcomes in learning theme 6 subtheme 1 at SD N 1 Batursari. This type of research is quantitative research using Pre Experimental design in the form of One Group Pretest-Posttest Design. The population of this study were all fifth grade students at SD Negeri 1 Batursari. The sample taken was 30 students, using saturated sampling technique. The data in this research was obtained through observation, interviews, tests and documentation. The data analysis technique used in the initial analysis was the normality test. The final analysis uses the normality test, hypothesis test, and learning completeness test. The average learning outcomes of students who showed learning without using the STEM learning model (pretest) was 48.6%. Meanwhile, the average learning outcomes of students after being treated (posttest) using the STEM learning model was 80.0%. This is reinforced by the results of the t test calculation. It can be concluded that the t test on the pretest and posttest results produces a significance value of 0.000 < 0.05, so H0 is rejected and Ha is accepted or it can be said that the STEM learning model has an effect on improving the learning outcomes of class V theme 6 students. subtheme 1 at SD N 1 Batursari. Based on the results of this research, the suggestions that researchers can convey are for teachers to use STEM learning models in learning activities.